Legal and moral and ethical problems of transplantation in Ukraine - Palchenkova, V. M.; Riabchynska, O.; Gorokhovska, O.; Stomatov, E.; Мирний, Сергій Петрович (My University, 2020)
ABSTRACT: The article analyzes the legal acts, modern scientific approaches to the implementation of transplantation as an alternative method of treatment of many diseases, as well as the state policy in this area, identifies the main legal and moral and ethical problems of transplantation in Ukraine, and makes recommendations for improving the state policy in the field of transplantation in order to solve them.Results. The main legal and bioethical problems of transplantation in Ukraine are: the absence of a legal definition of the concept of human death, specific methods of its detection; operating mechanisms of the national system of providing transplants (transplantation infrastructure), including the Unified state information system of transplantation, a mobile application to it, transplant coordinators, proven procedures, and so on; an effective state information policy aimed at promoting transplantation as a modern alternative method of treatment; proper legal regulation and effective state mechanisms for implementing bioimplantation.Methods. When writing the article, methods of search, analysis, synthesis, systematization and generalization of information, as well as thesociological method were used.Results. To solve legal and ethical problems of transplantation in Ukraine to improve the effectiveness of this treatment, it is necessary to implement a number of measures aimed at improvement of state policy in the field of transplantation. This is, first of all, the adoption of the Law of Ukraine "About death", which would define its clear criteria and methods of pronouncement. It is also necessary to adopt and actively implement the state program for the development of transplantation, which provides specific measures to digitalize this area, the introduction of clear procedures for the implementation of transplantation, the state information policy to promote transplantation and the development of bioimplantation.
Keywords: ransplantation; legal problems of transplantation; moral and ethical problems of transplantation; mechanisms and procedures of transplantation; presumption of "approval"; presumption of "refusal"; concepts of death; digitalization in transplantation; popularization of transplantation